Adolescent social housing protects against adult emotional and cognitive deficits and alters the PFC and NAc transcriptome in male and female C57BL/6J mice - Lodha, Jyoti; Brocato, Emily R.; Nash, McKenzie; Marcus, Madison M.; Pais, A. Chris; Pais, Alex B.; Miles, Michael F.; Wolstenholme, Jennifer Theresa (Frontiers in Neuroscience, 2023)
Adolescence is a critical period in cognitive and emotional development, characterized by high levels of social interaction and increases in risk-taking behavior including binge drinking. Adolescent exposure to social stress and binge ethanol have individually been associated with the development of social, emotional, and cognitive deficits, as well as increased risk for alcohol use disorder. Disruption of cortical development by early life social stress and/or binge drinking may partly underlie these enduring emotional, cognitive, and behavioral effects. The study goal is to implement a novel neighbor housing environment to identify the effects of adolescent neighbor housing and/or binge ethanol drinking on (1) a battery of emotional and cognitive tasks (2) adult ethanol drinking behavior, and (3) the nucleus accumbens and prefrontal cortex transcriptome. Adolescent male and female C57BL/6J mice were single or neighbor housed with or without access to intermittent ethanol. One cohort underwent behavioral testing during adulthood to determine social preference, expression of anxiety-like behavior, cognitive performance, and patterns of ethanol intake. The second cohort was sacrificed in late adolescence and brain tissue was used for transcriptomics analysis. As adults, single housed mice displayed decreased social interaction, deficits in the novel object recognition task, and increased anxiety-like behavior, relative to neighborhoused mice. There was no effect of housing condition on adolescent or adult ethanol consumption. Adolescent ethanol exposure did not alter adult ethanol intake. Transcriptomics analysis revealed that adolescent housing condition and ethanol exposure resulted in differential expression of genes related to synaptic plasticity in the nucleus accumbens and genes related to methylation, the extracellular matrix and inflammation in the prefrontal cortex. The behavioral results indicate that social interaction during adolescence via the neighbor housing model may protect against emotional, social, This is a provisional file, not the final typeset article and cognitive deficits. In addition, the transcriptomics results suggest that these behavioral alterations may be mediated in part by dysregulation of transcription in the frontal cortex or the nucleus accumbens.